Surface-guided radiotherapy systems in locoregional deep inspiration breath hold radiotherapy for breast cancer — a multicenter study on the setup accuracy - Laaksomaa, Marko; Aula, Antti; Sarudis, Sebastian; Keyriläinen, Jani; Ahlroth, Jenni; Murtola, Anna; Pynnönen, Kiira; Lehtonen, Tuukka; Björkqvist, Mikko; Järvinen, Lauri; Rossi, Maija (Via Medica, 2025)
Background: Daily image-guided radiotherapy (IGRT) and deep inspiration breath hold (DIBH) technique are recommended for locoregional RT of breast cancer. The optimal workflow for a combination of surface-guided RT (SGRT) with DIBH technique is of current clinical interest.
Materials and methods: The setup accuracy at three hospitals was evaluated using different SGRT workflows. A total of 150 patients (2269 image pairs) were analyzed in three groups: patient setup with the AlignRT® SGRT system in Tampere (Site 1, n = 50), the Catalyst™ SGRT system in Turku (Site 2, n = 50) and the Catalyst™ SGRT system in Jönköping (Site 3, n = 50). Each site used their routine workflow with SGRT-based setup and IGRT positioning. Residual errors of the bony chest wall, thoracic vertebra (Th 1) and humeral head were evaluated using IGRT images.
Results: Systematic residual errors in the cranio-caudal (CC) direction and in pitch were generally larger at Site 2 than those at Sites 1 and 3 (p = 0.01–0.7). With daily IGRT, only a small difference (p = 0.01–0.9) was observed in residual random errors of bony structures in other directions between sites.
Conclusion: The introduction of SGRT and the use of daily IGRT lead to small residual errors when combining the best workflow practices from different hospitals. Our multicenter evaluation led to improved workflow by tightening the SGRT tolerances on Site 2 and fixation modification. Because of mainly small random errors, systematic posture errors in the images need to be corrected after posture correction with new setup surfaces. We recommend tight SGRT tolerances, good fixation and correction of systematic errors.